Assessing the probability of purchasing an international brand alliance product in the context of perceived brand foreignness - Çağan, Hilal Öztay; Erol, Fuat (Eskişehir Osmangazi Üniversitesi, 2023)
The study aims to examine the effect of perceived brand foreignness towards the strategic brand alliance on the purchasing probability and the parallel mediating role of the attitude towards the brand alliance and the perceived quality of the brand alliance product in this relationship through the consumers of a developing country (i.e., Turkey). Also, the moderating effect of consumer cosmopolitanism on the effect of perceived brand foreignness upon attitude and perceived quality was investigated. According to the findings, perceived brand foreignness has a positive and significant effect on attitude and perceived quality. Moreover, the effect of perceived brand foreignness on purchase probability is mediated by both attitude and perceived quality. Finally, consumer cosmopolitanism has a moderating role in the effect of perceived brand foreignness on perceived quality.

Çalışmanın amacı, stratejik marka ittifakına yönelik algılanan marka yabancılığının tüketicilerin satın alma olasılığı üzerindeki etkisini ve bu ilişkide marka ittifakına yönelik tutumun ve marka ittifakı ürününe yönelik algılanan kalitenin paralel aracılık rolünü gelişmekte olan bir ülkenin (Türkiye) tüketicileri üzerinden incelemektir. Ayrıca algılanan marka yabancılığının tutum ve algılanan kalite üzerindeki etkisinde tüketici kozmopolitliğinin düzenleyici etkisi araştırılmıştır. Bulgulara göre algılanan marka yabancılığı, tutum ve algılanan kalite üzerinde olumlu ve anlamlı etkiye sahiptir. Dahası algılanan marka yabancılığının satın alma olasılığı üzerindeki etkisine tutum ve algılanan kalite aracılık etmektedir. Son olarak, algılanan marka yabancılığının algılanan kalite üzerindeki etkisinde tüketici kozmopolitliğinin düzenleyici rolü bulunmaktadır.

WOS:000971782600002
Keywords: Attitude Towards Brand Alliance; Strategic Brand Alliance; Perceived Brand Foreignness; Algılanan Marka Yabancılığı; Tüketici Kozmopolitliği; Consumer Cosmopolitanism; Marka İttifakına Yönelik Tutum; Algılanan Kalite; Perceived Quality; Stratejik Marka İttifakı